Mazhab Shahabi: Dinamika Fatwa Sahabat Mengenai Ba’i Al-Taqsith Dalam Pembiayaan Perumahan Syariah Pada Perbankan Syariah - Santi Arafah; Nurhayati; Anggraini, Tuti (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
The Mazhab Sahahabi is an alternative source of law after the Quran and Sunnah. The Sahabi madhhab is an opinion, theory, doctrine and belief in the form of a collective opinion of the Companions. This study aims to understand the dynamics of the fatwa of the companions regarding ba'i al-taqsith sharia housing. This research is qualitative with a library research approach, namely the data used in this research are sourced from various book literature related to the object of research, comparative techniques to conduct in-depth descriptive analysis in evaluating and comparing the various views of the Companions in dealing with Islamic legal issues. The results of the study state that the four shahabi mazhab allow bai' taqish in sharia housing finance in sharia banking as long as the transaction does not harm one of the parties and does not contain elements prohibited in Islam, such as usury or gharar.